SUPER POROUS HYDROGELS: A RECENT ADVANCEMENT IN GASTRORETENTIVE DRUG DELIVERY SYSTEM - Chordiya Mayur; Senthilkumaran K; Gangurde Hemant (Indonesian Journal of Pharmacy, 2013)
Super porous hydrogels (SPHs) were originally developed as a controlled drug delivery system to retain drugs in gastic medium. Super porous hydrogels (SPHs) are recent advancement in gastro retentive drug delivery system (GRDDS) which also includes intragastric floating system (low density system), mucoadhesive system, high density system and swellable system. Super porous hydrogels should instantly swell in the stomach and maintain their integrity in the harsh environment and release the pharmaceutical active ingredient. SPH swell fast, within minutes, the fast swelling property is based on water absorption through open porous structure by capillary force. This review discusses about the GRDDS, difference between gels and hydrogels and comparison between SAP vs. SPH. It also includes types of SPH, different generations, general synthesis, methods of preparations, gastric emptying, advantages, characterization, applications and salient features of SPH. Key words: Superabsorbent polymers (SAP), Super porous hydrogel (SPH), Gastro retentive drug delivery system